Phonological Analysis of the Students’ Speaking Performance in Delivering Short Stories - Purnami, Ni Made Ayu; Wedayanthi, Luh Made Dwi (Universitas Muhammadiyah Mataram, 2023)
Quintessentially, some significant proportions have arisen due to mistakenness carried out by the institute students in performing their speech demonstration, particularly in telling short stories. In essence, this current study is intended to anatomize the phonological errors in delivering short stories based on real-life experience. In addition, qualitative research method was used in this study especially in analyzing the utterances in the field of speaking aspect. It used data collection technique in the form of transcriptions. It is concluded that the findings of the study showed that the emersion of diverse variety which includes fluency, accuracy of the nature of phonology field is dominantly based on the background of education, environmental background, students’ motivation, learning atmosphere, students’ current efforts in learning language, and other internal and external factors which contributed. Encouragement from family and environment as one of external factor takes important role in order to improve the phonological mastery on students. According to the data gathered by the researcher, that phonological mistakenness executed by the students due to lack of learning English intensively and comprehending the nature of phonology.